Komunikasi Lintas Budaya pada Mahasiswa Perantauan di Universitas Islam Bandung - Riza Al Ghifari Suseno; Rini Rinawati (UNISBA Press, 2024)
Abstract. When someone decides to migrate, it means that he will enter a new environment with a new culture in it, not infrequently this difference makes it difficult for someone to survive in his new environment. Adaptation is one of the ways that a person needs to do when deciding to migrate. Adaptation is needed so that the individual can survive during the overseas period. In the process, each individual will have different experiences when trying to adapt. The objectives of this study are: 1) To find out the experience of overseas students from North Maluku in carrying out the adaptation process through cross-cultural communication at the Bandung Islamic University, 2) To find out the overseas students from North Maluku in the Mining Engineering study program in interpreting cross-cultural communication in the adaptation process, 3) To find out the motives of overseas students from North Maluku to do cross-cultural communication. The subjects of this study were students of the Mining Engineering Study Program at the Islamic University of Bandung who came from North Maluku. This research uses the constructivism paradigm, qualitative research method, and phenomenological approach. The theory used is Alferd Schutz's Phenomenology theory. The result of this study is that the adaptation experience carried out by students from North Maluku is divided into four phases, namely: 1) honeymoon phase, 2) frustration phase, 3) readjustment phase, 4) resolution phase. Regarding meaning, students from North Maluku interpret cross-cultural communication as a social norm, liaison, learning process, self-identity and character reflection. Meanwhile, the motive is divided into two parts, namely the cause motive which consists of 1) language differences, 2) daily needs, 3) realizing as foreigners Abstrak. Ketika seseorang memutuskan merantau artinya ia akan memasuki sebuah lingkungan baru dengan kebudayaan baru di dalamnya, tak jarang adanya perbedaan ini membuat seseorang menjadi sulit untuk bertahan berada di lingkungan barunya. Adaptasi merupakan salah satu cara yang perlu dilakukan oleh seseorang ketika memutuskan untuk merantau. Adaptasi dilakukan agar individu teresbut bias bertahan selama masa perantauan. Pada prosesnya, setiap individu akan memiliki pengalman yang berbeda-beda ketika berusaha beradaptasi. Tujuan dari penelitian ini adalah: 1) Untuk mengetahui pengalaman mahasiswa perantauan asal maluku utara dalam melakukan proses adaptasi melalui komunikasi lintas budaya di Universitas Islam Bandung, 2) Untuk mengetahui mahasiswa perantauan asal Maluku Utara program studi Teknik Pertambangan dalam memaknai komunikasi lintas budaya pada proses adaptasi, 3) Untuk mengetahui motif mahasiswa perantauan asal Maluku Utara melakukan komunikasi lintas budaya. Subjek pada penelitian ini adalah Mahasiswa Program Studi Teknik Pertambangan Universitas Islam Bandung yang berasal dari Maluku Utara. Penelitian ini menggunakan paradigma konstruktivisme, metode penelitian kualitatif, dan pendekatan fenomenologi. Teori yang digunakan adalah teori Fenomenologi Alferd Schutz. Hasil dari penelitian ini adalah pengalaman adaptasi yang dilakukan oleh mahasiswa asal Maluku Utara terbagi menjadi empat fase yaitu : 1) honeymoon phase, 2) frustration phase, 3) readjustment phase, 4) resolution phase. Terkait makna, mahasiswa asal Maluku Utara memaknai komunikasi lintas budaya sebagai norma sosial, penghubung, proses belajar, identitas diri dan cerminan karakter. Sedangkan pada motif terbagi menjadi dua bagian yaitu motif sebab yang terdiri dari 1) adanya perbedaan bahasa, 2) kebutuhan sehari-hari, 3) menyadari sebagai pendatang